CTT524 : Performance theory and style / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
The course introduces students to the techniques of performance (acting) styles in a theoretical manner. The performance styles are divided into classical, modern and postmodern. The course also covers Malaysian and Western styles of performance. Students will also be introduced to acting performance methods by Constantin Stanislavski, Bertolt Brecht, Harold Pinter, David Mamet, Meyerhold, Jerzy Grotowski, Antonin Artaud and Charles Marowitz.